BOLD Responses in Human Primary Visual Cortex are Insensitive to Substantial Changes in Neural Activity - Swettenham, Jennifer B.; Muthukumaraswamy, Suresh D.; Singh, Krish D. (Frontiers in Human Neuroscience, 2013)
The relationship between BOLD-fMRI (blood oxygenation level dependent-functional magnetic resonance imaging) and magnetoencephalography (MEG) metrics were explored using low-level visual stimuli known to elicit a rich variety of neural responses. Stimuli were either perceptually isoluminant red/green or luminance-modulated black/yellow square-wave gratings with spatial frequencies of 0.5, 3 and 6 cycles per degree. Neural responses were measured with BOLD-fMRI (3-tesla) and whole head MEG. For all stimuli, the BOLD response showed bilateral activation of early visual cortex that was greater in the contralateral hemisphere. There was variation between individuals but weak, or no evidence, of amplitude dependence on either spatial frequency or the presence of luminance contrast. In contrast, beamformer analysis of MEG data showed activation in contralateral early visual cortex and revealed: i) evoked responses with stimulus-dependent amplitude and latency; ii) gamma and high-beta oscillations, with spatial frequency dependent peaks at approximately 30 and 50 Hz, but only for luminance-modulated gratings; iii) The gamma and beta oscillations appeared to show different spatial-frequency tuning profiles; iv) much weaker gamma and beta responses, and at higher oscillation frequencies, for isoluminant compared to luminance-modulated gratings. The results provide further evidence that the relationship between the fMRI-BOLD response and cortical neural activity is complex, with BOLD-fMRI being insensitive to substantial changes in neural activity. All stimuli were clearly visible to participants and so the paucity of gamma oscillations to isoluminant stimuli is inconsistent with theories of their role in conscious visual perception.